Role of Salinity-Induced Barrier Layer in Air-Sea Interaction During the Intensification of a Typhoon - Hong, Ji-Seok; Moon, Jae-Hong; Kim, Taekyun; You, Sung Hyup; Byun, Kun-Young; Eom, Hyunmin (Frontiers in Marine Science, 2022)
A pronounced increase in the intensification of Typhoon Bavi in 2020 was detected when the typhoon passed over the Changjiang plume in the northern East China Sea. Using a coupled atmosphere-ocean modeling system, this study investigates the role of the plume-induced barrier layer (BL) in the air–sea interaction during the intensification of a typhoon. Simple comparative experiments with and without the river plume revealed a strong relationship between BL formation and typhoon intensification as a result of the significant surface freshening discharged from the Changjiang River. The plume-induced BL maintained a warm sea surface before the typhoon approached, thereby influencing the energy transfer at the air–sea interface. The enthalpy and moisture reaching the atmosphere were increased by approximately 20%, leading to the intensification of Typhoon Bavi and providing further support for the results observed in the best-track record. The model comparison also indicates that the salinity-induced BL led to the reduction of the typhoon-induced SST cooling by restricting the vertical diffusion between the surface and the thermocline, and consequently contributed to maintaining the typhoon intensity. This study suggests that the effect of river-induced surface freshening in a coupled atmosphere-ocean model may help in improving typhoon forecasts and may aid in mitigating against the destructive power of typhoons in the future.